Protein shakes for the brain [ 90 games and exercises to work your mind's muscle to the max - Noir, Michel , 1944-; Croisile, Bernard (New York : McGraw-Hill, 2009)
A quick brain boost filled with puzzles, memory games, and attention grabbers-all the ingredients you need to keep your brain young, healthy and in terrific shape!
1. Just starting out : easy exercises -- 2. Getting fit : medium exercises -- 3. Iron man : difficult exercises
Keywords: Brain; Intellect -- Problems, exercises, etc; Logic puzzles; Word games